Near-Infrared Luminescence and Single-Mode Laser Emission From Nd3+ Doped Compound Glass and Glass Microsphere - Wang, Xin; Zhao, Haiyan; Li, Angzhen; Tian, Ke; Brambilla, Gilberto; Wang, Pengfei (Frontiers in Materials, 2019)
In this letter, an Nd3+-doped compound fluorosilicate glass was successfully fabricated with the method of melt-quenching. Under the excitation of a 808 nm laser, enhanced near-infrared photoluminescence emission at the range from 1065 to 1140 nm was observed in the glass sample. To characterize its stability and resistance to environmental effects, transmission spectra at the range of NIR-MIR were measured under different environments, including humidity and temperature. In addition, the obtained fluorosilicate glass was also developed as a microsphere resonator by using CO2 laser heating method. When the diameter of the microsphere was controlled at 61.5 μm, coupling with a tapered fiber, single-multimode lasing in the wavelength range λ1056-1071 nm was achieved with a low lasing threshold of 1.5 mW. Compared to the traditional compound tellurate and fluoride glasses, this fluorosilicate glass has higher transition temperature; means that this resonator can be pumped by higher power. Therefore, using it as the raw material, the developed microsphere resonator offers a high transition temperature and with a low lasing threshold, which are promising it for high performance sensing and detection applications.